Гідродинамічна модель технологічного процесу безперервного лиття заготовок з кольорових металів та сплавів - Недорезов, С.С.; Хорошилов, О.М. (Видавничий дім "Академперіодика" НАН України, 2007)
We propose a hydrodynamic model adequately describing the technological process of continuous casting of the billets of non-ferrous metals and alloys. The full system of differential equations with the corresponding boundary conditions forming the basis of the given model is formulated and solved. A close fit of the theory with experimental data is got.